First study of different insect cells to triatoma virus infection - Susevich, Maria Laura (2015)
The use of viruses for biological control is a new option to be considered. The family Dicistroviridae, which affects only invertebrates, is one of the families that have been proposed for this purpose. The Triatoma virus (TrV), a member of this family, affects triatomine transmitters of Chagas disease, which is endemic in Latin America but also expanding its worldwide distribution. To this end, we attempted virus replication in Diptera, Aedes albopictus (clone C6/36) and Lepidoptera (Spodoptera frugiperda (SF9, SF21) and HighFive (H5) cell lines. The methodologies used were transfection process, direct inoculation (purified virus), and inoculation of purified virus with trypsin. Results were confirmed by SDS-PAGE, Western blotting, RT-PCR, electron microscopic and immunofluorescence. According to the results obtained, further analysis of susceptibility / infection of H5 cells to TrV required to be studied.